Birth Order, Parental Health Investment, and Health in Childhood - Gerald J. Pruckner; Nicole Schneeweis; Thomas Schober; Martina Zweimüller (Institute of Labor Economics (IZA), 2019)
This paper provides a comprehensive analysis of the relationship between birth order, health at birth and in childhood, and parental health investment using administrative data from Austria. We find significant birth order effects on health at birth and in primary school. These effects are positive, in that later-born siblings are healthier than the first-born child, and increase with birth order. Consequently, first-born children are more likely to consume medical drugs and to utilize medical services. We also find differences in parental health investment. First-born children are more likely to receive preventive medical care and immunization against measles, mumps, and rubella.
Keywords: I10; I12; I14; J12; J13; 330; birth order; parental health investment; parental health behavior; health at birth; health in childhood; health care utilization; vaccinations